Shifts in FGM/C practice in Sudan: communities' perspectives and drivers - Nafisa Bedri; Huda Sherfi; Ghada Rudwan; Sara Elhadi; Caroline Kabiru; Wafaa Amin (BMC, 2019)
Abstract Background Although Sudan has one of the highest prevalence of female genital mutilation or cutting (FGM/C), there have been shifts in e practice. These shifts include a reduction in the prevalence among younger age cohorts, changes in the types of FGM/C, an increase in medicalization, and changes in age of the practice. The drivers of these shifts are not well understood. Method Qualitative data drawn from a larger study in Khartoum and Gedaref States, Family and Midwife individual interviews and focus group discussions. Analysis and categorization within a Social Norms theoretical framework. Results Major findings confirmed shifts in the type FGM/C (presumably from infibulation to non-infibulating types) and increasing medicalization in the studied communities. These shifts were reported to be driven by social, professional and religious norms. Conclusion Changes in FGM practice in Sudan include drivers which will not facilitate abandonment of the practice instead lead to normalization of FGM/C. Yet professionalisation of Midwives including their oath to stop FGM/C has potential to facilitate abandonment rapidly if developed with other Sudan health professionals.